Significant structural evolution of a long‐term fallow soil in response to agricultural management practices requires at least 10 years after conversion. (22nd September 2020) - Bacq‐Labreuil, Aurelie; Neal, Andrew L.; Crawford, John; Mooney, Sacha J.; Akkari, Elsy; Zhang, Xiaoxian; Clark, Ian; Ritz, Karl
Abstract: Agricultural practices can have significant effects on the physical and biological properties of soil. The aim of this study was to understand how the physical structure of a compromised soil, arising from long‐term bare‐fallow management, was modified by adopting different field management practices. We hypothesized that changing agricultural practices from bare‐fallow to arable or grassland would influence the modification of pore structure via an increase in porosity and pore connectivity, and a more homogenous distribution of pore sizes, and that this change exerts a rapid evolution of soil structure following conversion. Soil aggregates (<2 mm) collected in successive years from field plots subjected to three contrasting managements were studied: bare‐fallow, bare‐fallow converted to arable, and bare‐fallow converted to grassland. Soil structure was assessed by X‐ray computed tomography on the aggregates at 1.5 μm resolution, capturing detail relevant to soil biophysical processes. The grassland system increased porosity, diversity of pore sizes, pore connectivity and pore‐surface density significantly over the decade following conversion. However, measured at this resolution, the evolution of most of these metrics of soil structure required approximately 10 years post‐conversion to show a significant effect. The arable system did not influence soil structural evolution significantly. Only pore size distribution was modified in grassland in a shorter time frame (2 years post‐conversion). Hence, evolution of soil structural characteristics appears to require at least a decadal timescale following conversion to grassland. Highlights: The physical structure of a compromised soil was modified by adopting plant‐based field management practices. Conversion to grassland increased pore size diversity after 2 years. Porosity, pore connectivity and pore surface density showed a significant modification between 7 and 10 years after conversion.